Constraints from Ligo o3 Data on Gravitational-Wave Emission Due to R-Modes in the Glitching Pulsar Psr J0537-6910 - Espinoza-Romo, C (IOP Publishing Ltd, 2021)
We present a search for continuous gravitational-wave emission due to r-modes in the pulsar PSR J0537-6910 using data from the LIGO-Virgo Collaboration observing run O3. PSR J0537-6910 is a young energetic X-ray pulsar and is the most frequent glitcher known. The inter-glitch braking index of the pulsar suggests that gravitational-wave emission due to r-mode oscillations may play an important role in the spin evolution of this pulsar. Theoretical models confirm this possibility and predict emission at a level that can be probed by ground-based detectors. In order to explore this scenario, we search for r-mode emission in the epochs between glitches by using a contemporaneous timing ephemeris obtained from NICER data. We do not detect any signals in the theoretically expected band of 86-97 Hz, and report upper limits on the amplitude of the gravitational waves. Our results improve on previous amplitude upper limits from r-modes in J0537-6910 by a factor of up to 3 and place stringent constraints on theoretical models for r-mode-driven spin-down in PSR J0537-6910, especially for higher frequencies at which our results reach below the spin-down limit defined by energy conservation. © 2021. The American Astronomical Society. All rights reserved..